2016
DOI: 10.1038/ajg.2016.267
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes of Rectal Neuroendocrine Tumors According to the Pathologic Status After Initial Endoscopic Resection: A KASID Multicenter Study

Abstract: Considering the long-term prognosis including that for recurrences or metachronous lesions, endoscopic resection is an efficient and a safe modality for the treatment of rectal NETs. This treatment may result in favorable clinical outcomes in patients with tumors of indeterminate pathology, as well as in pathologic tumor-free cases after initial resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 32 publications
2
33
0
1
Order By: Relevance
“…According to the current guidelines, lesions considered to be histologically non-curatively resected after ER must undergo additional salvage treatments 11 . However, the majority of patients with non-curative resection did not undergo additional salvage treatments 20 . The reason for patients not receiving additional treatments is that positive resection margins are not always predictive factors of remnant tumor, recurrence, or metastasis and that patients or clinicians decide to choose regular follow-up through colonoscopy and biopsy rather than salvage treatments.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current guidelines, lesions considered to be histologically non-curatively resected after ER must undergo additional salvage treatments 11 . However, the majority of patients with non-curative resection did not undergo additional salvage treatments 20 . The reason for patients not receiving additional treatments is that positive resection margins are not always predictive factors of remnant tumor, recurrence, or metastasis and that patients or clinicians decide to choose regular follow-up through colonoscopy and biopsy rather than salvage treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, and because of the extremely low risk of lymph node metastasis, local excision is considered to be a sufficient treatment for lesions less than 10 mm in diameter [ 5 ]. However, there are currently no widely used guidelines regarding the management of rectal NETs 10–20 mm in diameter [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that synchronous rectal NET at the initial diagnosis was associated with the development of development of metachronous rectal NETs [ 17 ]. Similar results were found in studies of colorectal adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al [14] reported that 7 of the 148 patients showed positive margins and therefore needed additional treatment. In patients with long-term follow-up with positive margins following endoscopic treatment without additional treatment, the local recurrence rate was 1.4% (2/141).…”
Section: Discussionmentioning
confidence: 99%